Differentiation Within An Organizational Population: Additional Evidence from The Wine Industry - Swaminathan, Anand; Delacroix, Jacques (Academy of Management Journal, 1991)
In this study of California wineries observed between 1940 and 1984, we showed that organizations within a population may escape competitive pressures through differentiation. Both wineries founded in the table wine niche and those that diversified into it were subject to lower failure rates than other wineries. This study also demonstrated how it is possible to compensate for a lack of strictly appropriate data, a characteristic of ecological studies.